Photovoice em pesquisas com gestantes: revisão de escopo e compreensão das barreiras de acesso aos serviços de saúde bucal - Lima, Caroline Meronha de [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
O Photovoice é uma metodologia de Pesquisa-Ação Participativa baseada na comunidade que utiliza a fotografia como ferramenta de expressão e reflexão crítica. Ao combinar o registro visual com a narrativa dos participantes, o método permite que grupos em situação de vulnerabilidade identifiquem, representem e comuniquem as realidades de suas vidas, promovendo o diálogo com gestores e a mudança social. Apesar da importância do cuidado durante a gestação, persistem barreiras subjetivas e desfechos negativos em acesso à saúde bucal que métodos de pesquisa tradicionais muitas vezes falham em captar. Esta dissertação estruturou-se em dois estudos para investigar o uso da metodologia Photovoice em pesquisas com gestantes e aplicá-la à compreensão das barreiras de acesso aos serviços de saúde bucal. O primeiro estudo, uma revisão de escopo conduzida segundo diretrizes do Joanna Briggs Institute e PRISMA-ScR, mapeou estudos globais que utilizaram o Photovoice com gestantes (Publicação 1). O estudo foi orientado pela questão de pesquisa: "Quais são os enfoques temáticos, desenhos metodológicos, contextos de aplicação e contribuições para a saúde pública dos estudos que utilizaram a metodologia Photovoice com gestantes?". Para responder a essa indagação, realizou-se uma busca sistemática nas bases de dados Web of Science, Google Scholar, PubMed, SciELO e Scopus. A revisão identificou oito estudos publicados entre 2013 e 2025, conduzidos em países da África, América Latina, América do Norte e Oceania, com predomínio de abordagens qualitativas que combinaram o Photovoice a entrevistas, grupos focais e outras técnicas participativas. Os enfoques temáticos identificados incluíram vulnerabilidades socioeconômicas, barreiras de acesso aos serviços, saúde mental, estigma, violência de gênero e empoderamento materno. A metodologia Photovoice foi aplicada sobretudo em contextos comunitários e de atenção primária, abrangendo populações urbanas, rurais e indígenas. Os achados evidenciam que o Photovoice permite captar dimensões subjetivas, sociais e culturais da gravidez, promovendo engajamento coletivo e protagonismo feminino. Como contribuição para a saúde pública, a metodologia Photovoice revelou lacunas de acesso, fortaleceu o senso coletivo e forneceu subsídios para políticas mais sensíveis às necessidades locais. O segundo estudo, com abordagem qualitativa, foi conduzido com gestantes usuárias do Sistema Único de Saúde em Araraquara-SP, utilizando o Photovoice (Publicação 2). Dezesseis gestantes, com idade entre 18 e 40 anos, alfabetizadas, usuárias do Sistema Único de Saúde e com período gestacional acima de 16 semanas, foram recrutadas em um serviço de saúde localizado em município de médio porte do estado de São Paulo. Cada gestante participou de três encontros presenciais e individuais com a pesquisadora, com duração aproximada de uma hora, ao longo de um intervalo de até dois meses. No primeiro encontro elas foram orientadas sobre o processo de Photovoice e foram coletadas informações sobre dados sociodemográficos. No segundo encontro, foram coletadas informações sobre comportamentos, necessidades, barreiras e incentivos de saúde bucal. No terceiro encontro, foram feitas discussões sobre as fotografias que retratavam as barreiras para o acesso a saúde bucal, onde as participantes compartilharam suas experiências na pesquisa, expressando como se sentiram ao compartilhar suas fotos e histórias com a pesquisadora. As narrativas e fotografias foram submetidas à análise pelo método Sort and Sift, Think and Shift© e interpretadas à luz do Modelo Comportamental de Utilização de Serviços de Saúde de Andersen. Embora 93,75% das participantes tenham manifestado desejo de realizar o pré-natal odontológico, o acesso aos serviços de saúde bucal mostrou-se bloqueado por uma interação complexa de fatores sistêmicos e psicossociais, categorizados em quatro eixos: (1) "O Cuidado Invisível", caracterizado pela falha sistêmica na informação e ausência de encaminhamento (fator capacitante contextual); (2) "A Sobrecarga da Mulher e o Cuidado Desumanizado", onde a exaustão física e a pressão social (fatores predisponentes) somam-se a atendimentos ríspidos que ferem a dimensão da aceitabilidade; (3) "Barreiras Estruturais", marcadas pela rigidez de horários e burocracia; e (4) "O Limite da Dor", refletindo uma cultura curativista e baixa percepção de necessidade preventiva. As seguintes intervenções para reduzir barreiras ao cuidado em saúde bucal foram propostas pelas gestantes: ampliação do acesso à informação por mídias sociais e grupos educativos; integração de consultas médicas e odontológicas e flexibilização de horários de atendimento; fortalecimento da humanização do atendimento; e expansão da oferta de serviços e das equipes de saúde bucal no SUS para melhorar o acesso. Conclui-se que as barreiras de acesso aos serviços de saúde bucal mostraram-se predominantemente sistêmicas e não apenas individuais. A garantia da integralidade no cuidado depende da institucionalização do pré-natal odontológico integrado ao médico e de estratégias ativas de comunicação, retirando da gestante o peso exclusivo pela iniciativa da busca pelo serviço.

Photovoice is a community-based participatory action research methodology that uses photography as a tool for expression and critical reflection. By combining visual records with participants' narratives, the method allows vulnerable groups to identify, represent, and communicate their life realities, promoting dialogue with policymakers and social change. Despite the importance of prenatal care, subjective barriers and negative outcomes in oral health access persist—challenges that traditional research methods often fail to capture. This dissertation was structured into two studies to investigate the use of Photovoice in research with pregnant women and to apply it to understanding the barriers to accessing oral health services.The first study, a scoping review conducted according to the Joanna Briggs Institute and PRISMA-ScR guidelines, mapped global studies using Photovoice with pregnant women (Publication 1). The study was guided by the research question: "What are the thematic focuses, methodological designs, application contexts, and public health contributions of studies that used the Photovoice methodology with pregnant women?". To answer this inquiry, a systematic search was performed in the Web of Science, Google Scholar, PubMed, SciELO, and Scopus databases. The review identified eight studies published between 2013 and 2025, conducted in countries across Africa, Latin America, North America, and Oceania, with a predominance of qualitative approaches that combined Photovoice with interviews, focus groups, and other participatory techniques. The identified thematic focuses included socioeconomic vulnerabilities, barriers to accessing services, mental health, stigma, gender-based violence, and maternal empowerment. The Photovoice methodology was applied primarily in community and primary care contexts, covering urban, rural, and indigenous populations. The findings evidence that Photovoice allows for the capturing of subjective, social, and cultural dimensions of pregnancy, promoting collective engagement and female protagonism. As a contribution to public health, the Photovoice methodology revealed access gaps, strengthened the collective sense, and provided evidence for policies more sensitive to local needs. The second study, with a qualitative approach, was conducted with pregnant women using the Unified Health System (SUS) in Araraquara-SP, using Photovoice (Publication 2). Sixteen pregnant women, aged between 18 and 40 years, literate, users of the Unified Health System, and with a gestational period above 16 weeks, were recruited from a health service located in a medium-sized municipality in the state of São Paulo. Each pregnant woman participated in three in-person and individual meetings with the researcher, lasting approximately one hour, over an interval of up to two months. In the first meeting, they were oriented on the Photovoice process, and sociodemographic data were collected. In the second meeting, information on oral health behaviors, needs, barriers, and incentives was collected. In the third meeting, discussions were held about the photographs depicting the barriers to oral health access, where the participants shared their experiences in the research, expressing how they felt sharing their photos and stories with the researcher. The narratives and photographs were submitted to analysis using the Sort and Sift, Think and Shift© method and interpreted in light of Andersen’s Behavioral Model of Health Services Use. Although 93.75% of the participants expressed a desire to undergo prenatal dental care, access to oral health services proved to be blocked by a complex interaction of systemic and psychosocial factors, categorized into four axes: (1) "Invisible Care", characterized by systemic failure in information and the absence of referral (contextual enabling factor); (2) "Women’s Overburden and Dehumanized Care", where physical exhaustion and social pressure (predisposing factors) are added to harsh treatments that harm the dimension of acceptability; (3) "Structural Barriers", marked by rigid schedules and bureaucracy; and (4) "The Pain Threshold", reflecting a curative culture and low perception of preventive need. The following interventions to reduce barriers to oral health care were proposed by the pregnant women: expanding access to information through social media and educational groups; integrating medical and dental consultations and making service hours more flexible; strengthening the humanization of care; and expanding the supply of services and oral health teams in the SUS to improve access. It is concluded that the barriers to accessing oral health services proved to be predominantly systemic and not just individual. Guaranteeing integrality in care depends on the institutionalization of prenatal dental care integrated with medical care and on active communication strategies, removing from the pregnant woman the exclusive burden of initiating the search for the service. Photovoice is a community-based participatory action research methodology that uses photography as a tool for expression and critical reflection. By combining visual records with participants' narratives, the method allows vulnerable groups to identify, represent, and communicate their life realities, promoting dialogue with policymakers and social change. Despite the importance of prenatal care, subjective barriers and negative outcomes in oral health access persist—challenges that traditional research methods often fail to capture. This dissertation was structured into two studies to investigate the use of Photovoice in research with pregnant women and to apply it to understanding the barriers to accessing oral health services.The first study, a scoping review conducted according to the Joanna Briggs Institute and PRISMA-ScR guidelines, mapped global studies using Photovoice with pregnant women (Publication 1). The study was guided by the research question: "What are the thematic focuses, methodological designs, application contexts, and public health contributions of studies that used the Photovoice methodology with pregnant women?". To answer this inquiry, a systematic search was performed in the Web of Science, Google Scholar, PubMed, SciELO, and Scopus databases. The review identified eight studies published between 2013 and 2025, conducted in countries across Africa, Latin America, North America, and Oceania, with a predominance of qualitative approaches that combined Photovoice with interviews, focus groups, and other participatory techniques. The identified thematic focuses included socioeconomic vulnerabilities, barriers to accessing services, mental health, stigma, gender-based violence, and maternal empowerment. The Photovoice methodology was applied primarily in community and primary care contexts, covering urban, rural, and indigenous populations. The findings evidence that Photovoice allows for the capturing of subjective, social, and cultural dimensions of pregnancy, promoting collective engagement and female protagonism. As a contribution to public health, the Photovoice methodology revealed access gaps, strengthened the collective sense, and provided evidence for policies more sensitive to local needs. The second study, with a qualitative approach, was conducted with pregnant women using the Unified Health System (SUS) in Araraquara-SP, using Photovoice (Publication 2). Sixteen pregnant women, aged between 18 and 40 years, literate, users of the Unified Health System, and with a gestational period above 16 weeks, were recruited from a health service located in a medium-sized municipality in the state of São Paulo. Each pregnant woman participated in three in-person and individual meetings with the researcher, lasting approximately one hour, over an interval of up to two months. In the first meeting, they were oriented on the Photovoice process, and sociodemographic data were collected. In the second meeting, information on oral health behaviors, needs, barriers, and incentives was collected. In the third meeting, discussions were held about the photographs depicting the barriers to oral health access, where the participants shared their experiences in the research, expressing how they felt sharing their photos and stories with the researcher. The narratives and photographs were submitted to analysis using the Sort and Sift, Think and Shift© method and interpreted in light of Andersen’s Behavioral Model of Health Services Use. Although 93.75% of the participants expressed a desire to undergo prenatal dental care, access to oral health services proved to be blocked by a complex interaction of systemic and psychosocial factors, categorized into four axes: (1) "Invisible Care", characterized by systemic failure in information and the absence of referral (contextual enabling factor); (2) "Women’s Overburden and Dehumanized Care", where physical exhaustion and social pressure (predisposing factors) are added to harsh treatments that harm the dimension of acceptability; (3) "Structural Barriers", marked by rigid schedules and bureaucracy; and (4) "The Pain Threshold", reflecting a curative culture and low perception of preventive need. The following interventions to reduce barriers to oral health care were proposed by the pregnant women: expanding access to information through social media and educational groups; integrating medical and dental consultations and making service hours more flexible; strengthening the humanization of care; and expanding the supply of services and oral health teams in the SUS to improve access. It is concluded that the barriers to accessing oral health services proved to be predominantly systemic and not just individual. Guaranteeing integrality in care depends on the institutionalization of prenatal dental care integrated with medical care and on active communication strategies, removing from the pregnant woman the exclusive burden of initiating the search for the service.
Photovoice in research with pregnant women: scope review and understanding of barriers to access to oral health services.
Keywords: Gestantes; Saúde bucal; Acesso efetivo aos serviços de saúde; Pesquisa participativa baseada na comunidade; Saúde materna; Pregnant people; Oral health; Effective access to healthservices; Community-based participatory research; Maternal health